Literature review and research issues: green aware cloud load balancing and scheduling techniques - Kalimuthu, Rajkumar; Thomas, Brindha (International Journal of Engineering and Technology, 2019)
The purpose of this paper is to present exploratory research of cloud federation service for the betterment of demand on basis of resource allocation, security and global environmental aware controls to review the literature, reports and research issues on tools/techniques/ methodologies. The current research paper highlights various definition, tools, techniques and methodologies in various researches and industries. This paper has been studied and adapted the researcherâ€™s scope, contribution and methodologies in cloud computing. Cloud computing is a new emerging technology to sharing of resource based on economic scale to achieve rationality. A cloud service can able access anywhere- any time in any of cost. In the provision of cloud service facing lot challenges to accomplish the user needs. Day by day number user access has increased so the cloud service provider (CSP) facing difficulty to deal the services in between server and client. The load balancing and scheduling techniques plays the major role of service management and cloud service provide want to achieve the goal of Quality of Service (QOS). Load balancer and scheduler are dynamically allocating and reallocating the task to respective sever with help of virtual machines. Sometimes the technology has imbalanced the services because of overload, duplication, automatic robot activities. It may lead the poor management service some cloud service provider are over utilized/underutilized, the consumption of fuel and emission of carbon also very high. In this review various techniques and algorithm are proposed to the load balancing and scheduling in Green Aware cloud system.Â Â